Legal Accountability of Political Parties in Election Financing and Ethics: A Normative and Empirical Study in Indonesia - Dziqry Abisha; Muhammad Haiban (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2026)
This research aims to analyze the forms and mechanisms of legal accountability of political parties in relation to election financing and the implementation of electoral ethics in Indonesia. As one of the pillars of democracy, political parties bear both legal and moral responsibilities to ensure elections are conducted in a fair, honest, and transparent manner. However, empirical findings indicate that violations of campaign finance regulations, non-transparent funding sources, and weak enforcement of legal sanctions against offenders remain prevalent. This study employs a normative juridical approach combined with empirical analysis through the examination of statutory regulations, decisions of electoral supervisory bodies. The results demonstrate that the existing regulatory framework governing political party financing lacks effective supervisory mechanisms, particularly in the areas of financial reporting and campaign fund auditing. Furthermore, sanctions for violations of electoral ethics are predominantly administrative in nature and rarely extend to criminal accountability.